Struktur dan Pola Komunikasi dalam Wacana Pembelajaran Teks Eksplanasi di Madrasah Aliyah Al-Istiqomah - Ari Wahyuni; Dian Eka Chandra Wardhana; Agus Trianto (LP4MK STKIP PGRI Lubuklinggau, 2020)
Learning explanatory text discourse can be seen whether it is successful or not in bringing students to achieve the goals of language learning by examining the structure and patterns of communication. For this reason, the purpose of this study is to describe the structure and patterns of communication in the discourse of explanatory text learning at Madrasah Aliyah Al-Istiqomah. The research method used a class discourse analysis model with the IRF model. The subjects of this study were 21 students. Data collection techniques are carried out by observation, recording, and interviews. Discourse analysis technique uses discourse analysis class Sinclair and Coulthard with the IRF model, namely initiation, response, and follow-up. Data validity test used triangulation of data collection techniques. The results showed that in learning explanatory text, the structure of classroom discourse in learning was not always structured with IRF in free exchange. Whereas in bound exchange, the function of F is not only reversed, but accompanied by re-initiation or bonding (Ib) so that the class discourse structure becomes IR Ib RF / Ib R. transaction communication.